Exogenous amino acids suppress glucose oxidation and potentiate hepatic glucose production in late gestation fetal sheep - Brown, Laura D. (Am J Physiol Regul Integr Comp Physiol, 2017)
Acute amino acid (AA) infusion increases AA oxidation rates in normal late gestation fetal sheep. Because the fetal oxygen consumption rate does not change with increased AA oxidation, we hypothesized that AA infusion would suppress glucose oxidation pathways and that the additional carbon supply from AA would activate hepatic glucose production. To test this, late gestation fetal sheep were infused intravenously for 3 h with saline or exogenous AA (AA). Glucose tracer metabolic studies were performed and skeletal muscle and liver tissues samples were collected. AA infusion increased fetal arterial plasma branched chain AA, cortisol, and glucagon concentrations. Fetal glucose utilization rates were similar between basal and AA periods, yet the fraction of glucose oxidized and the glucose oxidation rate were decreased by 40% in the AA period. AA infusion increased expression of PDK4, an inhibitor of glucose oxidation, nearly twofold in muscle and liver. In liver, AA infusion tended to increase PCK1 gluconeogenic gene and PCK1 correlated with plasma cortisol concentrations. AA infusion also increased liver mRNA expression of the lactate transporter gene (MCT1), protein expression of GLUT2 and LDHA, and phosphorylation of AMPK, 4EBP1, and S6 proteins. In isolated fetal hepatocytes, AA supplementation increased glucose production and PCK1, LDHA, and MCT1 gene expression. These results demonstrate that AA infusion into fetal sheep competitively suppresses glucose oxidation and potentiates hepatic glucose production. These metabolic patterns support flexibility in fetal metabolism in response to increased nutrient substrate supply while maintaining a relatively stable rate of oxidative metabolism.